Morphology and Electrical Properties of ITO Films Obtained on Silicon Substrates by CVD Method - Saidov, A.S.; Usmonov, Sh.N.; Khajiev, M.U.; Kutlimratov, A.; Ishniyazov, T.T.; Ismatov, N.B.; Ganiev, A.A.; Khajieva, S.M.; Juraev, Kh.N.; Tagaev, M.; Saidov, D.Sh.; Khudaybergenov, T.A. (East European Journal of Physics, 2025)
ITO films were obtained on silicon substrates using an improved chemical vapor deposition (CVD) method in a quasi-enclosed volume at normal atmospheric pressure, without using a carrier gas. The resulting films had a thickness of 2.8–3.0 microns and a fairly low sheet resistance. Using an SPM 9700HT type scanning probe microscope, the surfaces of 500×500 nm ITO film samples were examined, and the results are presented in the form of two-dimensional (2D) and three-dimensional (3D) images. The electrophysical properties of the grown films were studied by the Hall method and it was shown that the films have an n-type conductivity, a mobility of m ≈ 2.5 cm2/(V×s) and a concentration of charge carriers n ≈ 1.35×1020 cm-3 and a sheet resistance of r ≈ 1.85×10-5 W×sq-1 (ohms per square). It is shown that our modified method of chemical vapor deposition makes it possible to obtain ITO films with good characteristics acceptable for use in optoelectronics and photovoltaics devices as a transparent contact layer.